(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
As the Belt and Road Initiative (BRI) progresses into a high-quality development phase, transitioning from broad-brush concepts to detailed, actionable blueprints, production capacity cooperation between China and resource-rich Central Asian countries has deepened significantly